The Effect of COVID-19 on Tuberculosis Care and Treatment Outcome in Pre-COVID, COVID, and Post-COVID Eras - Pooja N. Ranpariya; Harsha M. Solanki; Rajesh K. Chudasama (Indian Journal of Community Medicine)
Background: Coronavirus disease 2019 (COVID-19) pandemic has caused a significant disruption of all healthcare services. Tuberculosis (TB) services were also affected by the COVID-19 pandemic policies. Therefore, this study was planned to observe whether TB services and treatment outcome were affected in pre-COVID, COVID, and post-COVID eras among TB patients. Materials and Methods: Secondary data analysis was carried out from the data obtained from District Tuberculosis Centre. Comparison of TB care data includes notification, diagnosis, treatment services, and outcome for the pre-COVID, COVID, and post-COVID periods. Results: TB notifications and diagnostic services were significantly hampered during the COVID-19 period as compared to pre-COVID and post-COVID periods (P < 0.05). However, in those diagnosed with TB, treatment was initiated timely and regular follow-up was done by health care workers to ensure treatment adherence, and hence, more cure rate was reported in the study. High mortality during COVID-19 period was found. Conclusion: TB care was significantly restrained during COVID-19 pandemic, and further reclamation of services occurred during the declining phase of COVID-19.